Stability of PGM-free fuel cell catalysts: Degradation mechanisms and mitigation strategies - Wan, Xin; Liu, Xiaofang; Shui, Jianglan (Progress in natural science, 2020)
While Platinum group metals (PGM) free catalysts are promising alternatives to expensive Pt as the cathode catalyst in proton exchange membrane fuel cells, their rapid degradation must be addressed for the commercial feasibility. This review provides a historical survey of the possible degradation mechanisms of PGM-free catalysts. Decades of extensive studies confirm that carbon oxidation and demetalation are primarily responsible for the instability, whereas the mechanisms of protonation and micropore flooding are strongly criticized. Based on the mechanism understanding, the mitigation strategies for improving stability are discussed in detail. Finally, some directions to achieve high-performance and durable PGM-free catalysts are proposed. [Display omitted] •Historical survey of the possible degradation mechanisms of PGM-free catalysts was provided.•Carbon oxidation and demetalation were identified as the most likely cause of instability of PGM-free catalysts.•Mitigation strategies for improving stability of PGM-free catalysts were summarized.